Antibiotic resistance patterns of urinary tract pathogens in children: current clinical challenges and therapeutic perspectives - Mahmoud Elmakkawy, Mariam Mahmoud Hassan; Zainudin, Zurina; Nunis, Melissa Anne; Mohamed Nashrudin, Khairoon Nisa; Ellias, Mohd Fahmi; Gad, Safwat Hassan (Ecronicon, 2024)
Urinary tract infections (UTIs) are common infections among children and are the most common proven bacterial infection in febrile infants without localising signs. UTIs are commonly caused by anatomical or functional abnormalities in the kidney and urinary tract. The effective management of urinary tract infections has become increasingly difficult due to significant resistance to frequently prescribed antibiotics, such as aminopenicillins, and the rising global prevalence of multidrug-resistant organisms responsible for these infections.